2015
DOI: 10.1021/acs.molpharmaceut.5b00351
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of the Physical Stability of Amorphous Anti-Inflammatory Agents: The Roles of Molecular Mobility and Molecular Interaction Patterns

Abstract: The aim of this article is to examine the crystallization tendencies of three chemically related amorphous anti-inflammatory agents, etoricoxib, celecoxib, and rofecoxib. Since the molecular mobility is considered as one of the factors affecting the crystallization behavior of a given material, broadband dielectric spectroscopy was used to gain insight into the molecular dynamics of the selected active pharmaceutical ingredients. Interestingly, our experiments did not reveal any significant differences in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 55 publications
4
56
0
Order By: Relevance
“…For example, telmisartan and etoricoxib exhibit, apart from the JG relaxation analysed in this work, a faster relaxation which has not been analysed here. 32,35 Also, as commented above, celecoxib exhibits a hidden and low intensity JG relaxation close to the structural relaxation. 38 The further remarkable decrease of the intensity of the secondary process in the USG precludes its analysis in this work.…”
Section: Resultsmentioning
confidence: 62%
“…For example, telmisartan and etoricoxib exhibit, apart from the JG relaxation analysed in this work, a faster relaxation which has not been analysed here. 32,35 Also, as commented above, celecoxib exhibits a hidden and low intensity JG relaxation close to the structural relaxation. 38 The further remarkable decrease of the intensity of the secondary process in the USG precludes its analysis in this work.…”
Section: Resultsmentioning
confidence: 62%
“…Black and red closed symbols correspond to the USG and the OG obtained after transformation of the USG and subsequent cooling down, respectively. The red open points and the orange VFT fit to t a in (B and C) are from the literature (etoricoxib, 14,16,17 telmisartan 18,19 ). All the data of toluene are extracted from Yu et al 13 The black and red circles indicate the value of t b at T on .…”
Section: Two General Properties Applied To Usgmentioning
confidence: 99%
“…The recommended dosage prescribed by medical doctors goes from 60 to 120 mg/day coming in 3 presentations (60, 90, 120 mg/tablet). 1,2,5,6 Etoricoxib (ETX) is considered a medium size drug with a molecular weight of 358.84 g/mol. It is synthesized from vinamidinium salts.…”
Section: Introductionmentioning
confidence: 99%
“…2 In this sense, there are several reports in the literature, which try to synthesize it in an amorphous form to overcome its water solubility issues. 6 In vitro and in vivo studies have shown a rapid absorption and a good bioavailability of ETX when taken orally. 2,10 Here, it is important to mention that ETX is part of the coxib family, which includes other related compounds such as celecoxib, valdecoxib and rofercoxib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation